(untitled) (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
The rapid integration of robotics and artificial intelligence (AI) into industrial and service sectors has redefined the landscape of labor. Automation, once perceived as a purely technical evolution, now stands at the crossroads of ethical inquiry—challenging fundamental concepts of human dignity, moral agency, and the purpose of work. This paper critically examines the ethical implications of robotic labor substitution, focusing on how automation reshapes human identity, responsibility, and economic participation. It explores philosophical, sociotechnical, and policy perspectives to argue that while automation enhances productivity, it must not erode human worth or autonomy. A balanced approach integrating ethical design, equitable labor transitions, and recognition of moral agency is essential to sustaining dignity in the age of intelligent machines.